2007
DOI: 10.1037/0882-7974.22.4.796
|View full text |Cite
|
Sign up to set email alerts
|

The aging decision maker: Cognitive aging and the adaptive selection of decision strategies.

Abstract: Are older adults' decision abilities fundamentally compromised by age-related cognitive decline? Or can they adaptively select decision strategies? One study (N = 163) investigated the impact of cognitive aging on the ability to select decision strategies as a function of environment structure. Participants made decisions in either an environment that favored the use of information-intensive strategies or one favoring the use of simple, information-frugal strategies. Older adults tended to (a) look up less inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
269
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 309 publications
(296 citation statements)
references
References 68 publications
25
269
1
1
Order By: Relevance
“…An additional sensitivity tests by including indicators for early, mid, and late trials in all regression models found no evidence of an association between learning and the outcomes. The lack of a learning effect may be attributable to the random order in which the choice tasks were presented and the discreteness of each task.This study provides the first empirical indications of why older adults are not choosing the lowest cost plan available under Part D. In partial support of earlier work (Mata et al, 2007), older adults' information search was less effective. Specifically, they were more likely to use an attribute-based rather than an alternative-based search approach.…”
mentioning
confidence: 51%
See 1 more Smart Citation
“…An additional sensitivity tests by including indicators for early, mid, and late trials in all regression models found no evidence of an association between learning and the outcomes. The lack of a learning effect may be attributable to the random order in which the choice tasks were presented and the discreteness of each task.This study provides the first empirical indications of why older adults are not choosing the lowest cost plan available under Part D. In partial support of earlier work (Mata et al, 2007), older adults' information search was less effective. Specifically, they were more likely to use an attribute-based rather than an alternative-based search approach.…”
mentioning
confidence: 51%
“…Johnson (1990Johnson ( , 1993 has provided evidence that when asked to select an apartment or a car older adults examined less information, reevaluated information more frequently, reviewed the information for longer time periods, and used more simplified search strategies. Others (Mata, von Helversen, & Rieskamp, 2010;Mata, Schooler, & Rieskamp, 2007) have investigated the effect of aging on the ability to select adaptive decision strategies in relation to different environmental structures. Their results show that older adults tend to use less information and take longer to process it, and they rely more often on simpler decision strategies because they lack the cognitive resources to use the more demanding ones.…”
Section: Age Decision Making and Strategy Selectionmentioning
confidence: 99%
“…As control variables, we also collected additional measures of cognitive capacity to assess participants' ability to deliberately control attention and manipulate information in working memory (digit span, symbol task, trail making test; see Mata et al 2007;Tombaugh 2004).…”
Section: Control Variablesmentioning
confidence: 99%
“…In individual 2-h sessions, each research participant completed the following tasks: 1) A preexperimental gambling questionnaire to assess participants' basic demographic information and their gambling involvment (e.g., games of play, frequency of engagement, amount of money they gamble with; see Winters, Specker, & Stinchfield, 1996), 2) a computerized sequential slot-machine choice task (Scheibehenne et al, 2011), 3) three short measures of cognitive capacity (Mata, Schooler, & Rieskamp, 2007) to assess participants' ability to deliberately control attention and manipulate information in working memory, 4) a shortened two-domain version of the Domain-Specific Risk-Attitude Scale (Weber, Blais, & Betz, 2002) to assess participants' likelihood of engagement in risk, their perceptions of risk and the expected benefits they attribute to risks in the gambling and investment domain, 5) a paper-and-pencil version of the DSM-based South Oaks Gambling Screen (Stinchfield, 2002) to screen for indications of problem gambling and pathological gambling, and 6) a paper-and-pencil version of the DSM-based two-item Lie/Bet Questionnaire (Johnson & Hamer, 1997) to screen for pathological gambling.…”
Section: Measures and Proceduresmentioning
confidence: 99%